Unmanned/Unattended Sensors and Sensor Networks 2004
DOI: 10.1117/12.578518
|View full text |Cite
|
Sign up to set email alerts
|

Optimal topologies for wireless sensor networks

Abstract: In this paper, we explore methods to generate optimal network topologies for wireless sensor networks (WSNs) with and without obstacles. Specifically, we investigate a dense network with n sensor nodes and m = n b (0 < b < 1) helping nodes, and assess the impact of topology on its throughput capacity. For networks without obstacles, we find that uniformly distributed sensor nodes and regularly distributed helping nodes have some advantages in improving the throughput capacity. We also explore properties of net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The sum of cognitive and personal components is generally set to four as recommended in [33]. In [34], they are set to 2.8 and 1.3, respectively. Although, based on our experiments, we adopt the values of 1.75 and 1.35, respectively.…”
Section: Pso and Nsga-iii Parametersmentioning
confidence: 99%
“…The sum of cognitive and personal components is generally set to four as recommended in [33]. In [34], they are set to 2.8 and 1.3, respectively. Although, based on our experiments, we adopt the values of 1.75 and 1.35, respectively.…”
Section: Pso and Nsga-iii Parametersmentioning
confidence: 99%
“…To decrease the loss of energy and data packets, a clustertree network topology structure (Tillett et al, 2004) (shown as Fig. 1) is applied in this design.…”
Section: Main Parameters Of Forest Fire Monitormentioning
confidence: 99%